2004
DOI: 10.1091/mbc.e03-09-0683
|View full text |Cite
|
Sign up to set email alerts
|

CIN85 Associates with Multiple Effectors Controlling Intracellular Trafficking of Epidermal Growth Factor Receptors

Abstract: CIN85 is a multidomain adaptor protein involved in Cbl-mediated down-regulation of epidermal growth factor (EGF) receptors. CIN85 src homology 3 domains specifically bind to a proline-arginine (PxxxPR) motif in Cbl, and this association seems to be important for EGF receptor endocytosis. Here, we report identification of novel CIN85 effectors, all containing one or more PxxxPR motifs, that are indispensable for their mutual interactions. These effectors include phosphatidyl-inositol phosphatases SHIP-1 and syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(139 citation statements)
references
References 65 publications
6
131
1
1
Order By: Relevance
“…The specific functions of ARAPs are largely unknown, although they appear to have roles in post-endocytic transport [52], cytoskeletal reorganization in response to growth factors [35], and focal adhesion dynamics [50]. Each of the ARAPs also contains a Ras-association (RA) domain, predicted to serve as a binding site for Ras or for closely related GTPases such as Rap [53].…”
Section: Arapsmentioning
confidence: 99%
“…The specific functions of ARAPs are largely unknown, although they appear to have roles in post-endocytic transport [52], cytoskeletal reorganization in response to growth factors [35], and focal adhesion dynamics [50]. Each of the ARAPs also contains a Ras-association (RA) domain, predicted to serve as a binding site for Ras or for closely related GTPases such as Rap [53].…”
Section: Arapsmentioning
confidence: 99%
“…In addition, Arf1 also mediates paxillin recruitment to focal adhesions (Norman et al, 1998). We have found that CIN85, a multidomain adaptor protein involved in Cbl-mediated down-regulation of EGFR, interacts with ASAP1, and overexpression of ASAP1 increases the recycling of EGFR in CHO cells (Kowanetz et al, 2004). More recently, CIN85 has been reported to colocalize with ASAP1 in invadopodia, and the complex of ASAP1 and CIN85 has been proposed to positively regulate the invasive phenotype of breast cancer cells (Nam et al, 2007).…”
mentioning
confidence: 94%
“…It was shown before that SHIP2 binds the E3 ligase Cbl and Cbl-associated protein (CAP) and SHIP2 is therefore suggested to have a role in endocytosis [29,35]. Furthermore, it was reported that Arap3 binds the adaptor protein CIN85 [13] and our screen identified the CIN85-related protein CMS as an Arap3 binding partner as well (Table 1). These two adaptor proteins both function in Cbl-mediated endocytosis [14].…”
Section: Discussionmentioning
confidence: 55%
“…Previously it was shown that Arap3 is present in a multimeric protein complex with the SH3 domain-containing protein CIN85 that binds Arap3 via a specific proline-arginine motif [13]. Our screen also identified the CIN85-related protein, CMS.…”
Section: Arap3 Is Part Of a Multimeric Protein Complexmentioning
confidence: 70%
See 1 more Smart Citation